Teacher Quality Dimensions in Improving the Quality of National Education at Madrasah Aliyah in Lampung - Dacholfani, Muhammad Ihsan; Wibowo, Agus; Fadillah, Muhammad Kharis (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This article explores the development of teacher quality dimensions in improving the quality of national education. Methods This research uses a case study with a mixed methods approach. The sampling technique uses a random sampling technique with respondents. Based on the findings in this study, the results of the analysis were obtained with a Satorra-Bentler Scaled Chi-Square value of 189.190 and a p-value coefficient of 0.070 > 0.05, RMSEA of 0.030 <0.080, CFI ≥ 0.90, so the model obtained is